Hubungan Pelaksanaan Penggunaan APD terhadap Kecelakaan Kerja di JOB Pertamina Talisman Jambi Merang - Peppy Herawati; Reza Khulaifi (Jurnal Daur Lingkungan, 2019)
This research is focused to approach at the relationship between the implementation of personal protective equipment (PPE) to  safety programme with employee, where PPE is used as a last resort in an effort to protect workers if the effort to control the elimination of danger sources, equipment substitution, engineering and administration but the potential risk is still relatively high. This research is focused on associative descriptive with correlation approach, which uses a questionnaire of 80 employees in the JOB Pertamina Talisman Jambi Merang production department engaged in the oil and gas industry located in Bayung Lencir, South Sumatra Province. The results of this study use a bivariate analysis test looking for the relationship between the application of personal protective equipment (PPE) with workplace accidents at the job accident on the crew driling the repair part of the well maintenance at the RPS 05 rig, PT.Pertamina EP Asset 1 Field Jambi. The study found that there was a significant relationship between the variables of K3 inspection and personal protective equipment (PPE) against work accidents. with a value (r) of 0.722 which means a significant relationship between the commitment to carry out K3 inspection and personal protective equipment (PPE). (PPE).